(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2010)
Recensiamo il libro di Bice Mortara Garavelli, Il parlar figurato. Manualetto di figure retoriche, Laterza, Roma – Bari, 2010.